Pelestarian kitab kuning di era modernisasi lembaga pendidikan pesantren - Al Haqiqy, Muhammad Sirajuddin (Maliki Interdisciplinary Journal, 2023)
The yellow book is an important part of the intellectual heritage in the Islamic scientific tradition, especially in pesantren, which is currently being lost due to the modernization of the education system. This article seeks to identify the challenges of preserving the yellow book and propose relevant strategies to ensure the continuity of this precious heritage. This article provides insight into the importance of maintaining a balance between salaf and modern education.